‘Failed States’ in Question and the Case of Sub-Saharan Africa - Kevin R. Cox (L'Espace Politique)
While the idea of the failed state can be easily contested as a Western conceit, understanding the symptoms typically claimed as indicating the condition is an important part of addressing it. A common argument has been that failure is a result of conditions internal to the country in question. This, though, is to ignore the way in which, in various ways, colonialism, and latterly a particular position in the international division of labor, have paved the way. In sub-Saharan African colonialism has been the more fundamental of the two. This is because of its failure to change production relations in a way that would encourage capitalist forms of development. A result has been the neo-patrimonial state which, in the context of dominantly pre-capitalist production relations, will necessarily struggle to achieve the standards held in the West to be successful.